Cadmium sulfide doped with silver as CO2 gas sensor using pyrolysis technique - Uday Ali Sabeeh Al-Jarah; Haidar Jawad Mohamad; Yahya Mustafa Abdul-Hussein (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The monitoring of CO2 in our life safety, industrial, and chemical laboratoryapplications make it an inspiring task. The chemical spray pyrolysis techniquewas used to prepare CdS/Ag thin films. The nanocrystalline cadmium sulfidethin films were doped with Silver at different doping concentrations (0%, 2%,and 4%). The morphologies, structures, and gas sensing properties of CdS/Agfilms are presented. The samples were characterized using X-ray diffraction(XRD) and atomic force microscope (AFM). The XRD results show that thefilms are a polycrystalline composition and hexagonal type with a favouredorientation along (111) direction. The average grain size (nm) of AFM isbetween 75 and 55 nm. As a result, Ag doping changes the sensitivity of thesamples respectively with the percentage of doping with time. The synthesissamples show controlling sensitivity and the small response of sensitivity arethe key point in this study.